STRUCTURE AND STAFF MOVEMENT WITHIN STATE VETERINARY SERVICE OF RUSSIAN FEDERATION - I. M. Klinovitskaya; M. A. Shibayev; A. V. Belchikhina; A. K. Karaulov (Ветеринария сегодня)
Major resources for any organization are human resources which condition the company’s performance. The article presents the analysis of quantitative and qualitative indicators of the number, structure and movement of staff of the state veterinary service of the Russian Federation in 2018. All indicators were examined at diff erent organizational levels of the veterinary service: the country’s veterinary service as a whole, at the level of the executive veterinary bodies of Russian subjects (including the state veterinary surveillance divisions), establishments for control and prevention and those for laboratory analysis and diagnosis. The work deals with the staff structure of the country’s state veterinary service categorized by education, length of service, age and gender. To study the movement of staff of the state veterinary service connected to recruitment and retirement of specialists, we calculated and analyzed a number of parameters: employee turnover rate for recruitment, employee turnover rate for leaving, total staff turnover rate, staff replacement rate. In 2018 the Russian state veterinary service comprised around 52,304 veterinary specialists, the majority of them (81%) being employed at establishments for control and prevention. The core of veterinary specialists is represented by employees with a university degree (75%), work experience of more than 10 years (55%), belonging to age group of 36–50 years (43%), female (62%). The results of analysis of human resources of the veterinary service allow us to determine the weak points of personnel policy and work out measures to deal with them if the need arises.